PERIODISASI PERKEMBANGAN HUKUM PERBANKAN SYARIAH DI INDONESIA - Santoso Santoso (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2015)
The rapid and siqnificant growth of Islamic banking must supported by qualified human resources. People need legal certainty to maintain social order. Sometimes, people make rules to legitimize their acts or to create a new interpretation of the law. Therefore, a strict law is required to control people from jumping to an apologetic conclusion. Islam provides human beings with God’s law as guidance in the world and the life here after. Islamic banking is a national banking system based on Islamic law. Islamic banking is founded based on Islamic economic system. It aims not only for profit but for people welfare.